Comparison of total artificial heart and biventricular assist device support as bridge‐to‐transplantation. Issue 10 (29th August 2016) - Cheng, Allen; Trivedi, Jaimin R.; Van Berkel, Victor H.; Massey, H. Todd; Slaughter, Mark S.
Abstract: BACKGROUND: The use of left ventricular assist devices (LVAD) has increased significantly in the last decade. However, right heart dysfunction remains a problem despite the improved outcomes with continuous‐flow LVADs. Surgical options for bridge to transplantation (BTT) in patients with biventricular failure are total artificial heart (TAH) or biventricular support (BiVAD). This study examines the differences in pre‐ and post‐transplantation outcomes and survival in patients with TAH or BiVAD support as BTT. METHODS: The United Network of Organ Sharing database was retrospectively queried from January 2005 to December 2014 to identify adult patients undergoing heart transplantation (n = 17, 022). Patients supported with either TAH (n = 212) or BiVAD (n = 366) at the time of transplantation were evaluated. Pre‐ and post‐transplantation Kaplan–Meier survival curves were examined. Cox regression model was used to study the hazard ratios of the association between TAH versus BiVAD support and post‐transplant survival. RESULTS: The median age of the study groups was 49.8 ± 12.9 (TAH) and 47.2 ± 13.9 (BiVAD) years (range 18–74 years). There were more men, 87% versus 74%, in the TAH group (p < 0.0001) with greater body mass index, 27.3 ± 5.2 versus 25.6 ± 4.7 (p < 0.0001), compared to those with BiVADs. Creatinine was higher, 1.7 + 1.2 versus 1.3 + 0.8 mg/dL (p < 0.0001), in the TAH group before transplant. The 30‐day, one‐, and three‐year post‐transplantation survival was 88%, 78%, and 67%, respectively, for patients with TAH support versus 93%, 83%, and 73% (p = 0.06) for patients with BiVAD support. Cox regression model shows pre‐transplant creatinine (HR = 1.21, p = 0.008) is associated with a lower post‐transplant survival. TAH is not associated with a worse post‐transplant survival (p = 0.1). There was no difference in wait‐list survival in patients supported with TAH or BiVAD (p = 0.8). CONCLUSION: Although there has been a recent increase in the use of the TAH as BTT, BiVAD support remains a viable option with similar post‐transplant survival.